Reservoir potential of the Eocene deltaic lacustrine system in the Pearl River Mouth Basin - Zhang, Yinglin; Sun, Hui; Xu, Leyi; Yan, Hui; Wang, Xiaomeng; Chen, Beichen (Frontiers in Earth Science, 2025)
With ongoing exploration and development in the Baiyun Sag, its southwestern portion has emerged as a promising target for significant hydrocarbon discoveries. However, commercial discoveries have yet to be achieved due to limited reservoir areal extent and tight reservoir properties. To resolve reservoir architecture and quality, we integrate seismic and core data, building a depositional-diagenetic model of the Eocene Enping Formation in the block L13. The results show that the Enping braid deltas, sourced from the Shunhe Uplift, contain HST delta-front channels that constitute the principal reservoirs. Reservoirs comprise feldspathic litharenite and litharenite, with moderate-low porosity (6.6–21.1%) and low-ultralow permeability (0.02–21.30 mD). Pore systems are typified by tuffaceous dissolution pores and feldspar dissolution pores, with reservoir quality governed by the interplay of depositional and diagenetic processes. Coarser-grained textures in delta-front subaqueous distributary channels provide favorable reservoir frameworks, whereas compaction dominates porosity-permeability reduction. The key factor in enhancing reservoir properties is the formation of intergranular dissolution pores, which arise from the dissolution of tuffaceous material and feldspar by CO2-organic acid fluids generated during source rock evolution. This work establishes a depositional-diagenetic framework for reservoir prediction in the Enping Formation, offering critical insights for unlocking tight gas potential in the underexplored southwestern Baiyun Sag.